First report of zucchini tigre mosaic virus infecting four cucurbit crops in China - Zhou, Cuiji (Plant disease, 2022)
Cucurbits including ridge gourd (Luffa acutangula), Chieh-qua (Benincasa hispida Cogn. var. Chieh-qua How), Trichosanthes anguina, and sponge gourd (L. cylindrica) are important vegetables in most Asian countries. The 90 viruses known to infect cucurbits include 15 species in genus Potyvirus. In October 2020, nine cucurbit samples with leaf distortion, blister and mottle were collected from the same field of Foshan City, Guangdong Province, China. All samples were tested by western blot with potyvirus-specific antibody (Agdia lnc., Elkhart, IN) and RT-PCR with potyvirus degenerate primers Sprimer/M4T (Chen et al. 2001). Seven out of nine samples were positive for potyvirus in both tests, including one ridge gourd, one Chieh-qua, one sponge gourd, two bottle gourd (Lagenaria siceraria) and two T. anguina. All PCR products (~700-bp) were cloned and sequenced. Sequences of seven amplicons (OM522614 to OM522618, OP090158 to OP090159) containing partial nib and cp genes shared 80.3-100% nucleotide (nt) identity among themselves, and 81.2-97.7% nt identity with ZTMV isolates from China (MN267689, LC371337, MK988416). Except for one Chieh-qua sample, papaya ringspot virus (PRSV) was detected in the same samples where ZTMV was found through sequencing of the amplicons mentioned above. The obtained sequences (OM808942 to OM808945, OP090170 to OP090171) were 95.4-100% identical with PRSV isolates from China. Further RT-PCR was conducted with ZTMV-specific primers ZTMVdF/ZTMVdR targeting partial P3 and 6K1 genes, and PRSV-specific primers PRSV3778F/PRSV4630R targeting partial P3, full-length 6K1 and partial CI genes for all nine samples. Consistently, seven samples were positive for ZTMV, among which one Chieh-qua sample was infected with only ZTMV and six samples were co-infected with ZTMV and PRSV. Interspecific recombination event has been reported for ZTMV (Peng et al. 2021), to detect the recombinants, RT-PCR was conducted for all nine samples with primers ZTMV600F/ZTMV2400R covering the interspecies recombination site (Peng et al. 2021). A fragment (~1.8 kb) was amplified from one T. anguina sample and sequenced (OP090172), which had 97.0% nt identity with the reported recombinant ZTMV-KF17 (MK988415). To fulfill Koch's postulates, a Chieh-qua sample detected with ZTMV but not PRSV, was used for mechanical inoculation on Chieh-qua seedlings. Blister and leaf distortion similar to the field symptoms were observed 21 days post-inoculation. ZTMV infection was verified by RT-PCR with primer pairs Sprimer/M4T and ZTMVdF/ZTMVdR, respectively, followed by sequencing. No amplicon was detected with primer pairs PRSV3778F/PRSV4630R and ZTMV600F/ZTMV2400R. To study the incidence of ZTMV and PRSV, 33 samples including T. anguina, ridge gourd and Chieh-qua were collected from three different fields in Foshan City in May 2022, and were tested by RT-PCR with ZTMV and PRSV primers aforementioned. 30.3% (10/33) of the samples were positive for ZTMV, 39.4% (13/33) tested positive for PRSV, and 21.2% (7/33) were co-infected with the two viruses. Amplicons of ZTMV (600 bp) from all positive samples were sequenced (OP090160 to OP090169), and were 84.8-85.5% identical with ZTMV-TW (LC371337). Recombinant of ZTMV was detected in one T. anguina with primers mentioned above and was sequenced (OP090173), which had 96.2% nt identity with ZTMV-KF17. To our knowledge, this is the first report of ZTMV infecting ridge gourd, Chieh-qua, T. anguina and sponge gourd. The results implied that ZTMV had a potential risk to more cucurbit crops in the field